(3GdCKGQ hSjGSGJ GdGUdGM(B: (3JLGQH eNJGQIs - (3aVjd(B, (3QGjSs ((3GdLRGFQ(B:s (3GdfTQ GdLGeYj GdLOjO(B,s, 2021)
(3aj GdYOjO ef GdHdOGf jJe JTLjY EfJGL hGSJNOGe GdhbhO GdCMahQj ef NdGd GdOYe GdSNj GdPj JJMedg GdMcheGJ aj ejRGfjGJgG, hjSGge gPG GdOYe aj JdhK GdghGA hGdGROMGe GdeMdj, hGSJfRGa ehGQO eGdjI VNeI, hQZe cd gPG GdOYe dG jUd Edi CabQ GdCSQ aj GdZGdH, ceG Cf HQGeL GdOYe gPg JRGMe GdGSJKeGQ aj GdJYdje hGdUMI hcPG GdWGbI GdfXjaI, hJTLY GdGSJgdGc GdeaQW ddWGbI, hjecf Cf jSGYO GUdGM eKd gPg GdGYGfGJ aj GdMO ef GdJdhK hJMSjf UMI GdGfSGf, hJMQjQ GdGjQGOGJ GdYGeI, hGdJj jecf GSJNOGegG dJfajP SjGSGJ GdGbJUGO GdCNVQ hOYe GdChdhjGJ GdCNQi, haj GdSfhGJ GdCNjQIJe JHfj GdYOjO ef GdJRGeGJ GdGUdGM hLghO GdeQGbHI hgPG HeTGQcI GdYOjO ef GdefXeGJ GdYGdejI, ceG Cf SjQI fLGM GdcKjQ ef GdOhd hefgG Ohd YQHjI aj gPG GdeLGd CUHMJ YGed VZW hJMajR aj faS GdhbJ dHbjI GdHdOGf ef CLd GdeVj bOeG aj gPG GdOQH(B.s
(3eQGLY U(B.147s
Keywords: (3GdJfejI GdGbJUGOjI (B- (3GdHdOGf GdfGejIs; (3GdWGbIs; (3GdefXeI GdYGdejI ddJLGQIs